Malaysian endophytic fungal extracts-induced anti-inflammation in Lipopolysaccharide-activated BV-2 microglia is associated with attenuation of NO production and, IL-6 and TNF-α expression - Harun, Azzeme (BMC Complement Altern Med, 2015)
BACKGROUND: Excessive production of inflammatory mediators such as nitric oxide (NO) and proinflammatory cytokines like tumour necrosis factor-alpha (TNF-α) from activated microglia contributes to uncontrolled inflammation in neurodegenerative diseases. This study investigated the protective role of five endophytic extracts (HAB16R12, HAB16R13, HAB16R14, HAB16R18 and HAB8R24) against LPS-induced inflammatory events in vitro. These endophytic extracts were previously found to exhibit potent neuroprotective effect against LPS-challenged microglial cells. METHODS: The effects of these fungal endophytic extracts against nitric oxide (NO), CD40 phenotype and, pro- and anti-inflammatory cytokine production in lipopolysaccharide (LPS)-stimulated BV2 microglia cells were examined using commercially available assay kits, immunophenotyping and flow cytometry, respectively. RESULTS: Microglia pre-treated with the five endophytic extracts (0.1 mg/mL) reduced NO production without compromising cell viability. Whilst CD40 expression in LPS-stimulated microglia was not significantly different with or without the influence of endophytic extracts, expression of the proinflammatory cytokines, IL-6 and TNF-α in LPS-stimulated microglia was significantly (P < 0.05) inhibited by these endophytic extracts. CONCLUSIONS: The outcomes suggest that the neuroprotective effect of the fungal endophytic extracts is likely mediated through supression of neuroinflammation. To our knowledge, this is the first report of the effect of a fungal endophytic extract in controlling inflammation in BV2 microglia cells. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12906-015-0685-5) contains supplementary material, which is available to authorized users.